Doctor Atomic [opera in two acts] - Sellars, Peter 1957-; Finley, Gerald 1960-; Rivera, Jessica 1974-; Owens, Eric 1970-; Fink, Richard Paul; Maddalena, James 1954-; Rabiner, Ellen; Renes, Lawrence (Opus Arte, 2008)
J. Robert Oppenheimer began an experiment that formed a threat to the whole of humanity, and whose scientific results still do today. The question of the moral implications of the atomic bomb is raised in Adams opera.
Interpr. u.a.: Gerald Finley (J. Robert Oppenheimer). Jessica Rivera (Kitty Oppenheimer). Eric Owens (General Leslie Groves). Richard Paul Fink (Edward Teller). James Maddalena (Jack Hubbard). Thomas Glenn (Robert Wilson). Jay Hunter Morris (Captain James Nolan). Ellen Rabiner (Pasqualita). Ruud van Eijk (Lieutenant Bush). Netherlands Philharmonic Orchestra. Chorus of de Nederlands Opera. Lawrence Renes [Dir.]. Peter Sellars [Regie]. - Live-Aufn.: Amsterdam, Het Muziektheater, Juni 2007. - Enth. Bonus-Material
Keywords: Sellars, Peter -- Interviews; Atomic bomb -- Drama; Operas; DVD-Video; Nonfiction films; Televised operas; Opera - Performance